Towards the development of the Claret High School mathematics achievement test - Canizares, Ma. Perpetua Cortez (Animo Repository, 1987)
The Claret High School Mathematics Achievement Test (CHSAT) was developed to measure achievement of Grade VI pupils of the said school. The steps followed in the construction of the test were: 1. planning the test, 2. developing the test specifications, 3. constructing the test items, 4. administering the pretest forms, 5. analysis of the pretests, and 5. preparing the final form. The characteristics of the items were determined through item analysis which was processed by the Center for Educational Measurement (CEM). This analysis provided the basis for selecting the items to compose the final form of the test. Acceptable difficulty index ranges from a p of .10 to .90 while acceptable discrimination index ranges from .30 and above. Attractiveness of options was also determined (at least 8 percent of N should choose a distracter). The final form is composed of 50 items to be administered in 60 minutes. The index of discrimination of the final form ranges from .28 to .68 which could be considered moderately discriminating while the difficulty index (p) ranges from .13 to .74 which is also considered of moderate difficulty. It can be concluded that among the content areas, Whole Numbers is considered to be the easiest (x = .46) while the hardest is Percentages (x = .34).